Protopanaxatriol-type saponin protects against acetaminophen-induced liver injury through ROS-mediated JNK pathway. (November 2021) - Qu, Linlin; Fu, Rongzhan; Ma, Xiaoxuan; Fan, Daidi
Graphical abstract: Highlights: PTS could lowered APAP-induced liver injury. PTS decreased APAP-induced liver inflammation. PTS restored the oxidative stress in APAP-induced liver injury mice. PTS inhibited APAP-induced apoptosis. PTS could regulate JNK pathway. Abstract: Worldwide, drug-induced acute liver failure is associated with a high rate of morbidity and mortality. Acetaminophen (APAP), a widely used analgesic, is one of the most common causes of acute liver injury. The purpose of this study was to determine the protective effect of protopanaxatriol-type saponin (PTS) against APAP-induced liver injury and to elucidate the mechanisms underlying this effect. Mice were pretreated with PTS via gavage for 7 days prior to receiving APAP. The results indicated that PTS was highly effective in preventing hepatotoxicity caused by APAP. Meanwhile, pretreatment with PTS resulted in a decrease in inflammation and oxidative stress. Furthermore, PTS reversed the histological change and reduced hepatic injury. Additionally, PTS inhibited the expression of proteins associated with APAP induced hepatic apoptosis in the liver. Taken together, our findings indicated that PTS protected against liver injury caused by APAP by alleviating oxidative stress, inflammation, and apoptosis via the ROS-mediated JNK pathway. Our findings suggest that PTS may have the potential as a novel therapeutic agent for APAP-induced liver injury.